KARO’S LOCAL WISDOM: THE USE OF WOODY PLANTS FOR TRADITIONAL DIABETIC MEDICINES - Situmorang, Rospita Odorlina; Harianja, Alfonsus H.; Silalahi, Johansen (Indonesian Journal of Forestry Research, 2015)
This paper identifies the plant species used traditionally by Karo people in North Sumatra, to cure diabetes, analyses the cultural significance index of those plants for the Karo, and clarifies phytochemical contents of the plants. Data were collected using survey method from selected respondents (n=54) based on their knowledge and practices in utilising medicinal plants to cure diabetic disease. Index of Cultural Significance (ICS) of plants was determined using the method proposed by Turner. Results showed that twelve woody plant species have been used to cure diabetes: loning leave (Psychotria sp.), kacihe leave (Prunus accuminta Hook), umbrella tree leave (Maesopsis eminii Engl), mutamba leave (Guazuma ulmifolia Lamk), cepcepan leave (Villebrunea subescens Blume), pirdot/cepcepan lembu leave (Saurauia vulcani Korth), raru bark (Cotylelobium melanoxylo), breadfruit leave (Artocarpus altilis), salam leave (Syzygium polyanthum Wight), mahogany seed (Swietenia mahagoni (L.) Jacq), cinnamon bark (Cinnamomum burmani), and yellow bamboo rod (Bambusa vulgaris Schrad). Five of those plants: loning, umbrella tree, mutamba, raru and salam have the highest cultural significance level. These five plants are highly needed in large quatities by the Karo people, so their availability in the forest should be securely conserved and protected. The plants used contained alkaloids, flavonoids, phenolics and terpenoids which can help to lower blood sugar level.